Mechanical Forces Exacerbate Periodontal Defects in Bsp-null Mice. (September 2015) - Soenjaya, Y.; Foster, B.L.; Nociti, F.H.; Ao, M.; Holdsworth, D.W.; Hunter, G.K.; Somerman, M.J.; Goldberg, H.A.
Bone sialoprotein (BSP) is an acidic phosphoprotein with collagen-binding, cell attachment, and hydroxyapatite-nucleating properties. BSP expression in mineralized tissues is upregulated at onset of mineralization. Bsp -null ( Bsp -/- ) mice exhibit reductions in bone mineral density, bone turnover, osteoclast activation, and impaired bone healing. Furthermore, Bsp -/- mice have marked periodontal tissue breakdown, with a lack of acellular cementum leading to periodontal ligament detachment, extensive alveolar bone and tooth root resorption, and incisor malocclusion. We hypothesized that altered mechanical stress from mastication contributes to periodontal destruction observed in Bsp -/- mice. This hypothesis was tested by comparing Bsp -/- and wild-type mice fed with standard hard pellet diet or soft powder diet. Dentoalveolar tissues were analyzed using histology and micro–computed tomography. By 8 wk of age, Bsp -/- mice exhibited molar and incisor malocclusion regardless of diet. Bsp -/- mice with hard pellet diet exhibited high incidence (30%) of severe incisor malocclusion, 10% lower body weight, 3% reduced femur length, and 30% elevated serum alkaline phosphatase activity compared to wild type. Soft powder diet reduced severe incisor malocclusion incidence to 3% in Bsp -/- mice, supporting the hypothesis that occlusal loading contributed to the malocclusion phenotype. Furthermore, Bsp -/- mice in the soft powder diet group featured normal body weight, long bone length, and serum alkaline phosphatase activity, suggesting that tooth dysfunction and malnutrition contribute to growth and skeletal defects reported in Bsp -/- mice. Bsp -/- incisors also erupt at a slower rate, which likely leads to the observed thickened dentin and enhanced mineralization of dentin and enamel toward the apical end. We propose that the decrease in eruption rate is due to a lack of acellular cementum and associated defective periodontal attachment. These data demonstrate the importance of BSP in maintaining proper periodontal function and alveolar bone remodeling and point to dental dysfunction as causative factor of skeletal defects observed in Bsp -/- mice.